Wave Solutions of an a-cut Uniaxially Crystal - M, B. Daariimaa; G. Ochirbat; J. Khatanbaatar; P. Munkhbaatar (Scientific transaction of the National University of Mongolia. Physics, 2022)
We consider the problem of a plane wave refraction on an a-cut uniaxially crystal. We show that ordinary and extraordinary waves in Kerr medium could be the plane wave with amplitude and wavevector independent of coordinates. The another result is that the problem of polarization of the isoradial wave in a biaxial crystal is reformulated. The driven equation is slightly dierent the equation given in Ref.[2]. We solved problem for eigenvalues and eigenvectors of polarization of the electric eld for the isoradial wave.